Learning to fail : the tragedy of T.H White’s romance fantasy the once and future king - Leong, Darryl Kah Ming (2014)
When Cornelia Funke, best-selling author of teenage fantasy fiction, calls The Once and Future King (OFK) the “book of a lifetime”, she meant it in both senses of the phrase. To her, reading White’s novel was a unique and life-changing experience that planted the seeds for her eventual writing career. But she also paid homage to White’s depiction of the entire life story of King Arthur from his youth to his death. It is a “book that grows up” together with its main protagonist, beginning with youthful idealism and gradually maturing towards its tragic denouement (Lupeck 213). It is no secret that White based his fantasy on Thomas Malory’s Arthurian romance Le Morte d’Arthur, having written his bachelor’s thesis on it, but he was not interested in merely re-telling the Arthurian myth. In 1938, White wrote to a friend recounting his excitement, whilst re-reading Malory, at discovering that “(a) The thing was a perfect tragedy, with a beginning, a middle and an end implicit in the beginning and (b) the characters were real people with recognisable reactions which could be forecast” (White 86). However, those were not effectively achieved by Malory and so he set about “the task of interpreting Le Morte d’Arthur for the modern reader, particularly for the young and inexperienced reader who needed to be drawn in to what is still for many people at the present day an inaccessible work” (Brewer 18). This endeavour materialised in a five part volume of works, each depicting an important segment of King Arthur’s development, like the five acts of a Shakespearean tragedy. However, this was eventually published, due to post-war scarcity of resources, as a four-part volume. The last book, The Book of Merlyn, was left out, but not before White transferred key scenes into The Sword in the Stone, the first book of the volume, as well as others. White named his volume of works “The Once and Future King” after the inscription of Arthur’s tombstone in Malory’s compilation: ‘Hic iacet Arthurus, rex quondam rexque futurus’, which translates to ‘Here lies Arthur, the once and future king’. But while Malory’s work was a compilation of various Arthurian romances, White’s was an endeavour to “bridge the gap between medieval ways of thinking and our own” (Brewer 19).